The Subjective Impact of Separation and Divorce on a Latency-Aged Child and His Analysis. Issue 1 (1st January 2019) - Bram, Anthony D.
ABSTRACT: I present the analysis of a latency-aged child whose parents separated about one-and-a-half years into treatment and subsequently divorced. Even prior to his parents' announcement, the patient was preoccupied by intense anxieties about separation and abandonment. Such anxieties were exacerbated by the dissolution of his parents' marriage and of his familiar family constellation. I begin with a brief overview of the child's early development, the recommendation for analysis, and the initial phase of treatment. I then focus on process material from a two-year span following the parental separation. My aim is to illuminate the child's subjective experience of parental separation and divorce and my analytic efforts to help him represent, communicate, and understand it.